Continued Breastfeeding as Perceived by Ownership Index Quintile: Secondary Data from the 2023 Indonesian Health Survey - Siti Rapingah; Eka Nurhayati; Nova Muhani; Rohman Daka; Febrianti Harum Ningtyas (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: The WHO recommends breastfeeding until two years of age to support health and prevent stunting, but breastfeeding sustainability in Indonesia remains low. This study aims to analyze factors associated with breastfeeding sustainability in children aged 12 and 23 months in Indonesia using secondary data from the 2023 Indonesian Health Survey (SKI). Methods: This cross-sectional quantitative study involved 10.769 children aged 12-23 months from 345.000 toddler households, selected through purposive sampling with inclusion criteria (mothers without twins, last child, no specific disease, child without congenital abnormalities) and exclusion (incomplete data), using a two-stage sampling technique (census block PPS and systematic household sampling). Data were analyzed using bivariate ( chi-square ) and multivariate analysis. Result: The result  showed a significant relationship between ownership index quintile, exclusive breastfeeding, , maternal education, place of birth, ANC staff, and ANC location, with p-values of <0.001 (<0.005) respectively, and the continuation of breastfeeding, but the ANC variable was not related, with a p-value of 0.062. The location or place of ANC at the maternity hospital/clinic was the main predictor with a value (AOR 1.5; 95% CI: 1.2 - 1.9), indicating that mothers who underwent ANC examinations at maternity home/clinics were 1.5 times more likely to continue breastfeeding after controlling for other variables Conclusion: Socioeconomic disparities influence access to maternal health services. Breastfeeding sustainability is influenced by socioeconomic factors, facilities, and health services